2021
DOI: 10.3390/jcm10173762
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implants for Refractory Macular Edema in Eyes with Noninfectious Uveitis

Abstract: Macular edema (ME) is a common cause of visual loss among eyes with uveitis, and its management can be challenging. Steroids are an effective treatment for ME, and intravitreal dexamethasone (DEX) implants provide sustained steroid release. The purpose of this study is to evaluate intravitreal DEX implant on refractory ME in eyes with noninfectious uveitis. A retrospective study including 52 eyes of 37 patients with refractory uveitic ME was conducted from January 2011 through August 2017 at Linkou Chang Gung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…4 Subsequent real-world studies showed that functional and anatomic responses to DEX are not always favourable, 5 and MO may persist in up to 50% of cases. [6][7][8][9][10] There is a knowledge gap regarding the clinical and morphologic factors predicting the response to intravitreal DEX in NIU MO patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Subsequent real-world studies showed that functional and anatomic responses to DEX are not always favourable, 5 and MO may persist in up to 50% of cases. [6][7][8][9][10] There is a knowledge gap regarding the clinical and morphologic factors predicting the response to intravitreal DEX in NIU MO patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Subsequent real-world studies showed that functional and anatomic responses to DEX are not always favourable, 5 and MO may persist in up to 50% of cases. [6][7][8][9][10] There is a knowledge gap regarding the clinical and morphologic factors predicting the response to intravitreal DEX in NIU MO patients.Optical coherence tomography (OCT) allows a repeatable evaluation of central macular thickness (CRT) and retinal layers' integrity. 11 Previous studies showed only a moderate correlation between visual acuity (VA) and CRT; 12 thus, alternative biomarkers explaining VA variability in NIU MO patients must be identi ed.…”
mentioning
confidence: 99%
“…We performed a mixed model analysis based on the intent-to-treat approach to evaluate the time-varying 3-month, 6-month, and 12-month changes in LogMAR VA, CRT, and IOP, since these outcomes were repeatedly measured during the follow-up period [ 29 ]. The mixed model analysis factored in the assessment time points, the different groups, and the interaction between these two parameters as fixed effects and among individual patients as random effects.…”
Section: Methodsmentioning
confidence: 99%
“…However, the outcomes of DEXi are not always favorable with up to 50% of UME patients being unresponsive or partly responsive. In addition, the durability of DEXi does not exceed four to six months [ 9 , 11 , 12 , 13 , 14 , 15 ], implying the recourse to iterative invasive intravitreal procedures. In this vein, sustained release implants offer an interesting alternative, allowing a longer-term quiescence.…”
Section: Introductionmentioning
confidence: 99%